A survey on internal and external factors influencing students’ English fluency development at grade 11 in an upper secondary school in Vinh Phuc province - Khổng, Thị Thảo (2020)
This research aims to investigate the internal and external factors that affectstudents’ fluency development for grade 11th at Tran Phu Upper Secondary School – Vinh Phuc province and suggest some solutions to the problems. The data of the research was collected from both students’ and teachers’ questionnaires and classroom observation before and after treatment. The findings revealed that both teachers and students at Tran Phu Upper Secondary School are facing many problems in improving fluency for students, specifically speaking skill. Through this research, many factors have been listed such as learning styles, students’ habit of usingmother tongue, students’ low motivation and low English level accounting for poor vocabulary, structure, and poor pronunciation. Some factors from teachers are teaching large and mixed level classes, references, resources and time pressure. From the findings, suggestions are given with hope that they may be a reliable and useful source of reference for not only teachers but also students at Tran Phu Upper Secondary School to develop students’ fluency in a cooperative learning environment.